INCREASED INVOLVEMENT HEALTH CADRES OF THE STUNTING ACCELERATION TEAM: KASI JENTING (KADER SIAP DETEKSI JEJARING STUNTING) - Hartati, Sri; Ayu, Shinta Arini; Prasetyo, M Dodik; Hasbyalloh, M Salman; Shirly, Salma Fadilah; Hanapi, Ali; Saputra, Moch Surya; Pratiwi, Alya Azzahra (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
According to the World Health Organization (WHO), stunting is a developmental disorder in children caused by malnutrition, recurrent infections, or inadequate psychosocial stimulation. Stunting refers to a condition in which the length or height of an infant is shorter than its age and sex. This community service activity (PkM) was carried out in the Ciherang Health Center Working Area, Karangtengah District, Cianjur Regency to Posyandu Health Cadres. The methods used in this community service activity are counseling, discussion, and evaluation through pre-test and post-test. The results of the activity showed an increase in participants' understanding of stunting. This counseling succeeded in providing insight to participants about efforts to prevent stunting.